Clinical features of atypical tuberculosis mimicking bacterial pneumonia - Qi Min (De Gruyter, 2021)
The aim of this study is to investigate clinical features of atypical pulmonary tuberculosis (aPTB) mimicking bacterial pneumonia, determine imaging features with the highest degree of correlation, and identify predictors for acid-fast bacilli (AFB) positivity.